MILK FATTY ACID COMPOSITION IN HOLSTEIN COWS UNDER CHRONIC HEAT STRESS CONDITIONS - V. Danchuk; S. Midyk; V. Korniyenko; O. Izhboldina; N. Cherniy; А. Sydelnykov; V. Postoi; R. Mylostyvyi (Harčova Nauka ì Tehnologìâ)
This experiment was carried out to study the effect of temperature-humidity index (THI) and chronic heat stress on the intensity of fatty acid secretion by the mammary gland of Holstein cows. Twenty-five mature Holstein cows (130±25 days of lactation) with a daily milk yield of 30 kg were randomly assigned to one group. Morning milk was collected from these cows in spring, summer (high temperatures), and autumn, and the fatty acid profile of milk lipids was determined at comfortable temperatures of keeping and under conditions of chronic heat stress. Nineteen fatty acids were quantitatively determined in the milk of experimental cows by the gas chromatography method. Myristic (C14:0), palmitic (C16:0), stearic (C18:0), and oleic (C18:1n9c) fatty acids have the highest percentage content. These studies confirmed that long periods of heat can affect the quantitative composition of fatty acids in milk lipids. As a result of research, it was found that the THI can be used to predict the performance and milk fatty acid composition in lactating high-yielding cows of the Holstein breed. Under the values of THI 58 and 66, the intensity of lactation in cows and the fatty acid composition of the obtained milk did not differ significantly, although trends to changes were observed for individual fatty acids. An increase in the value of THI to 74 caused both a significant increase in the total content of unsaturated fatty acids (UFAs) in the milk of Holstein cows, as well as monounsaturated (MUFAs) and polyunsaturated (PUFAs), which was accompanied by a decrease in SFAs/UFAs ratio to the level of 1.87. This value was significantly lower than that of cows' milk collected in May and November. The increase in the relative content of milk fatty acids in Holstein cows at THI of 74 occurs mainly due to fatty acids with 18 carbon atoms in the chain. Thus, the relative content of C18:1n9c under conditions of chronic heat stress (THI 74) was 26.75±1.27, this value is 4.07% higher than in milk collected in May at THI of 66 and by 4.21% higher than in milk collected in November at THI of 58.